ОПТИМІЗАЦІЯ РЕГУЛЯТОРІВ ЧАСТОТНО КЕРОВАНИХ АСИНХРОННИХ ЕЛЕКТРОПРИВОДІВ ПРИ СТОХАСТИЧНИХ НАВАНТАЖЕННЯХ - Шуруб, Ю.В.; Дудник, А.О.; Лавінський, Д.С. (Інститут електродинаміки НАН України, Київ, 2016)
Optimization criteria of regulating laws for frequency controlled induction electric drives under the stochastic loads is formed. Possibility of energy efficiency increasing of electric drives due to using the statistically optimal regulators is showed. Mathematical models and transfer functions of regulating circuits of flux of induction motors in power optimization mode for vector control algorithm are proposed. They implemented by frequency converters with the properties of the current source and voltage source. Recommendations for using the optimal regulators of induction electric drives under the stochastic loadings and frequency control depending on the spectral characteristics of the loadings are developed. References 5, figure 1.